(3eYQaI cSha GdTeSs
(3ChdgG (B:s
(3EPG cGf GdGLJeGY fgGQkG hGdTeS bQjHI ef GMOi GdYbOJjf hcGf YQV GdbeQ ai GdLfhH Cbd ef (B( (3dg (B) (3ObjbI s
(3BNQgG (B:s
(3Ke ROfG SGYGJ GdSbhW Ydi SGYGJ hSW GdcSha HdZ (B( (3W dhdH (B) (3hgh JeGe GdGfLdGA hgj eOI Ref GdcSha hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3ef U (B120 - (3U(B140s
(3HgG LOGhd cKjQIs
(3HgG fXGe GdJYbjHIs
(3cJHJ JYde ajg bdjd ef GdVHW heged GdfbW CMjGfkGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
Keywords: (3Gdadcs